2009
DOI: 10.3748/wjg.15.1958
|View full text |Cite
|
Sign up to set email alerts
|

Rocket “Eruca sativa”: A salad herb with potential gastric antiulcer activity

Abstract: Rocket extract possesses anti-secretory, cytoprotective, and anti-ulcer activities against experimentally-induced gastric lesions. The anti-ulcer effect is possibly through prostaglandin-mediated activity and/or through its anti-secretory and antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 43 publications
2
77
0
2
Order By: Relevance
“…The prevalence of this disease can lead to occur more often due to excessive drinking of alcohol, smoking, stress, infections, nutritional deficiency, abrupt use of nonsteroidal drugs for managing anti‐inflammatory diseases (NSAIDs); it is a multietiologic chronic disease (Alqasoumi, Al‐Sohaibani, Al‐Howiriny, Al‐Yahya, & Rafatullah, 2009; Gisbert, 2005; Süleyman et al., 2009). Pathologically, digestive ulcers located in the gastric and duodenal mucosa induce acute erosive and surface desquamatious ulcerative lesions following exposure to gastric juices, including gastric acid and pepsin (Alqasoumi et al., 2009; Huh et al., 2003). Disorders or decreases in gastric mucosa antioxidant defense systems have been implicated in the pathogenesis and progression of various gastric ulcers (Kwiecień, Brzozowski, Konturek, & Konturek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this disease can lead to occur more often due to excessive drinking of alcohol, smoking, stress, infections, nutritional deficiency, abrupt use of nonsteroidal drugs for managing anti‐inflammatory diseases (NSAIDs); it is a multietiologic chronic disease (Alqasoumi, Al‐Sohaibani, Al‐Howiriny, Al‐Yahya, & Rafatullah, 2009; Gisbert, 2005; Süleyman et al., 2009). Pathologically, digestive ulcers located in the gastric and duodenal mucosa induce acute erosive and surface desquamatious ulcerative lesions following exposure to gastric juices, including gastric acid and pepsin (Alqasoumi et al., 2009; Huh et al., 2003). Disorders or decreases in gastric mucosa antioxidant defense systems have been implicated in the pathogenesis and progression of various gastric ulcers (Kwiecień, Brzozowski, Konturek, & Konturek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…of glucosides, mineral salts and vitamin C and is therefore considered to be an excellent stomachic stimulant (Alqasoumi et al 2009, Katsarou et al 2016. E. sativa seed oil has antioxidant and antimicrobial properties (Khoobchandani et al 2010) and serves to inhibit the proliferation of tumour growth (Azarenko et al 2014).…”
mentioning
confidence: 99%
“…Moreov er, Alq asoumi (2010) reported that Er uca s ativ a extract protec t the liver against CCl4-i nduc ed hep atic inj ur y through its pot ent anti oxidant a ctivit y i n rats . Histopat hological st udies ( Alqasoumi et al , 2009) et al, 2009). It has been rep orted that t he r ocket seed poss ess es pot ent antioxidant and r enal prot ectiv e char act eristics ( Mahran et al, 1991;Yaniv et al, 1998;S arwar et al , 2007;Alqas oumi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%